2018
DOI: 10.1038/s41467-018-02998-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of diborenes and their 90°-twisted diradical congeners

Abstract: Molecules containing multiple bonds between atoms—most often in the form of olefins—are ubiquitous in nature, commerce, and science, and as such have a huge impact on everyday life. Given their prominence, over the last few decades, frequent attempts have been made to perturb the structure and reactivity of multiply-bound species through bending and twisting. However, only modest success has been achieved in the quest to completely twist double bonds in order to homolytically cleave the associated π bond. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
8

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 55 publications
5
64
0
8
Order By: Relevance
“…Simulations based on DFT and multi-reference calculations were carried out for 3 , 4 and 5 . While DFT often provides very accurate geometries and frequencies even for molecules with complicated electronic structures, 48 it is in many cases less accurate for the computation of energy surfaces or excitation energies. 49 Hence, the ωB97X-D3 50 functional was employed for frequency computations, but the multi-reference NEVPT2 51 approach was used to determine geometrical changes and to compute ionization energies as well as the energy difference between the two relevant states of the [BiCH 3 ] •+ cation ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…Simulations based on DFT and multi-reference calculations were carried out for 3 , 4 and 5 . While DFT often provides very accurate geometries and frequencies even for molecules with complicated electronic structures, 48 it is in many cases less accurate for the computation of energy surfaces or excitation energies. 49 Hence, the ωB97X-D3 50 functional was employed for frequency computations, but the multi-reference NEVPT2 51 approach was used to determine geometrical changes and to compute ionization energies as well as the energy difference between the two relevant states of the [BiCH 3 ] •+ cation ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in 5 and 5-thf, the B1-C1 and C1-N1 bonds at the neutral CAAC Me ligand (1.5174(18) and 1.4601(18)Å, respectively) are within the range typical of partial double bonds, as is typical for CAAC-stabilised boryl radicals due to the delocalisation of the unpaired electron over the N1-C1-B1 p framework. [5][6][7][8][9]21,22,[31][32][33] The IR spectrum of 6 shows a B-H stretching band at 2533 cm À1 (calc. : 2558 cm À1 at uB97XD/6-31+G*), ca.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas P-H bond activation at transition 25 and main-group 26 metal centres is well documented, to the best of our knowledge the sole reported example of hydrophosphination of a homonuclear double bond comprising elements other than carbon is the 2016 report by Wang and Wu of hydrophosphination of the N]N bond in azobenzene with diphenylphosphine oxide. 27 Recent studies in our laboratories have demonstrated the feasibility of adding H-H, 28,29 B-H, [30][31][32] B-B, 33,34 S-S 35,36 and Se-Se 35 bonds across boron-boron multiple bonds. In this work, we show that uncatalysed hydrophosphination of both diborenes and diborynes can be used as a mild, selective and catalyst-free route to construct B-P bonds.…”
Section: Introductionmentioning
confidence: 99%